Plasma neurofilament light chain as a biomarker for fatal familial insomnia. (7th March 2022) - Hermann, Peter; Canaslan, Sezgi; Villar‐Piqué, Anna; Bunck, Timothy; Goebel, Stefan; Llorens, Franc; Schmitz, Matthias; Zerr, Inga
Abstract: Background and purpose: Fatal familial insomnia is a rare hereditary prion disease associated with the D178N‐129M PRNP mutation. Early diagnosis is difficult, because the clinical syndrome may overlap with affective disorders. In addition, most known cerebrospinal fluid biomarkers for prion diseases and magnetic resonance imaging do not show a good diagnostic accuracy for fatal familial insomnia. In this context, data on plasma biomarkers are scarce. Methods: We analyzed levels of neurofilament light chain, glial fibrillary acidic protein, chitinase‐3‐like protein 1, calcium‐binding protein B, and total tau protein in six serial plasma samples from a patient with fatal familial insomnia. Subsequently, plasma neurofilament light chain was analyzed in n = 25 patients and n = 19 controls. The diagnostic accuracy and associations with disease stage and duration were explored. Results: Among all biomarker candidates in the case study, only neurofilament light chain levels showed a constant evolution and increased over time. They discriminated fatal familial insomnia from controls with an area under the curve of 0.992 (95% confidence interval [CI] = 0.974–1) in the case–control study. Higher concentrations were associated with methionine homozygosity at codon 129 PRNP ( p = 0.006), shorter total disease duration (rho = −0.467, p = 0.019, 95% CI = −0.790 to −0.015), and shorter time from sampling to death (rho = −0.467, p = 0.019, 95% CI = −0.773 to −0.019). Conclusions: Plasma neurofilament light chain may be a valuable minimally invasive diagnostic biomarker for fatal familial insomnia after clinical onset. Most important, stage‐related increase and association with disease duration indicate potential as a prognostic marker and as a surrogate marker in clinical trials. Abstract : We investigated plasma biomarkers during preclinical and clinical phase in a patient with fatal familial insomnia (FFI) and identified a stage‐related increase of neurofilament light chain (NfL) from disease onset to late clinical stage. In a retrospective analysis, we observed high discriminatory value of plasma NfL in 25 FFI patients versus 19 control patients (area under the curve = 0.992). In FFI, higher NfL concentrations were significantly associated with shorter overall disease duration and shorter time from sampling to death.